Immersive Virtual Reality eHealth Intervention to Reduce Anxiety and Depression in Pregnant Women: Randomized Controlled Trial (Preprint) - Marta Jimenez-Barragan; Amparo Del Pino Gutierrez; Gloria Sauch Valmaña; Olga Monistrol; Carme Monge Marcet; Mar Pallarols Badia; Ignasi Garrido; Anna Carmona Ruiz; Oriol Porta Roda; Cristina Esquinas; Gemma Falguera Puig (2025)
BACKGROUND Mental health during pregnancy is a critical factor influencing maternal and fetal outcomes. Anxiety and depression affect up to 30% of pregnant women, with significant consequences for maternal well-being and child development. Despite this, interventions during pregnancy remain limited, creating a need for innovative, accessible solutions. OBJECTIVE This study aimed to evaluate the effectiveness of an immersive virtual reality (IVR) eHealth intervention in reducing anxiety and depression symptoms in women during pregnancy. METHODS A 2-arm, randomized controlled trial was conducted across 5 primary care centers in Catalonia, Spain, between October 2021 and May 2024. The study included pregnant women (N=70) aged ≥18 years with moderate anxiety and depression symptoms (Edinburgh Postnatal Depression Scale [EPDS] scores: 9-12) at 12 to 14 weeks of gestation. They were randomly assigned (1:1) to an IVR intervention or standard care group. The intervention group engaged in daily 14-minute IVR mindfulness and relaxation sessions for 6 weeks. Mental health outcomes were assessed using the EPDS and State-Trait Anxiety Inventory. RESULTS The intervention group demonstrated significant reductions in EPDS scores, with a mean decrease from 11.32 (SD 0.96) to 7.25 (SD 1.32; P<.001), compared to an increase in the control group from 11.32 (SD 0.94) to 16.23 (SD 1.25; P<.001). Similarly, State-Trait Anxiety Inventory scores improved markedly in the intervention group (mean decrease from 57.94, SD 5.23 to 35.03, SD 6.12; coefficient –30.47, 95% CI −45.23 to −15.72; P<.001), while the control group experienced a nonsignificant increase (from 66.10, SD 5.89 to 72.91, SD 6.34; P=.68). High adherence rates were observed, with 79% (26/33) of participants completing ≥30 sessions. Participant satisfaction was high, with 87% (29/33) reporting being “very satisfied” with the intervention. CONCLUSIONS The IVR eHealth intervention significantly reduced symptoms of anxiety and depression, demonstrating its potential as an accessible and effective tool for mental health support during pregnancy. High adherence and satisfaction levels underscore its feasibility and acceptability. Future research should explore the long-term effects and scalability of IVR interventions in diverse settings. CLINICALTRIAL ClinicalTrials.gov NCT05756205; https://clinicaltrials.gov/study/NCT05756205 INTERNATIONAL REGISTERED REPORT RR2-10.1186/s12912-023-01440-4